A Novel Treatment of Opioid Cravings With an Effect Size of .73 for Unilateral Transcranial Photobiomodulation Over Sham - Schiffer, Fredric; Reichmann, William; Flynn, Edward; Hamblin, Michael R.; McCormack, Hannah (Frontiers in Psychiatry, 2020)
Background: Opioid use disorders (OUD) are an epidemic causing catastrophic consequences to individuals, families, and society despite treatments including psychotherapy, substitution therapy or receptor blockers, and psychoeducation. We have developed a novel treatment that combines transcranial photobiomodulation (t-PBM) and Dual Brain Psychology (DBP) Methods: We used a randomized, double-blind, placebo-controlled protocol in which 22 patients with significant opioid cravings and a history of recent or current OUD attended three one-hour weekly sessions. After baseline measures of opioid craving, and other psychometrics, subjects received two unilateral t-PBM applications (810 nm CW LED, 250 mW/cm2, 60 J/cm2, 4 min) or a sham (foil-covered LED) at F3 or F4. Prior to any treatment we used 2 tests to determine which hemisphere was more associated with a negative outlook and cravings and treated that side before the more positive hemisphere. Primary outcome measure was an opioid craving scale (OCS). plus weekly Hamilton Depression (HDRS) and Anxiety (HARS) Rating Scales prior to treatments. Results: Immediately after treatment the OCS improved significantly for both the sham and active treatments, but one week later the active treatment showed a 51.0% (SD 33.7) decrease in OCS while a week after the sham treatments there was a decrease of only 15.8% (SD 35.0) (1-sided paired t-test, p = 0.0041). The effect size for the active treatment was 1.51 and for the sham, 0.45. The HDRS improved from a baseline of 15.1 to 8.8 (SD 10.3) a week after the active treatment and to 13.3 (SD 12.9) after the sham (p = 0.0087). HARS improved from 14.7 to 8.0 (SD 13.2) after the active treatments and to 14.3 (SD 16.0) after the sham. Real-treatment of the positive hemisphere after the negative significantly improved the OCS, but there was no significant difference after the sham. One patient complained of abdominal bloating and dropped out, no other adverse effects were observed. Discussion: Unilateral t-PBM to the hemisphere with a more positive hemispheric emotional valence was an effective and safe treatment for opioid cravings as well as for depression and anxiety. Our results also lend support to the underlying premise of DBP.